Nitrogen efficiency by soil quality and management regimes on Malawi farms: Can fertilizer use remain profitable? - Burke, William; Jayne, Thom; Snapp, Sieglinde S. (Elsevier, 2022)
Maize is the primary economic and dietary staple crop for most poor farmers in Southern Africa, yet low yields have persisted in the region for decades. Intensifying maize production in a sustainable way using the same land will be increasingly important as virgin land becomes scarcer and fallowing becomes less common. This study investigates the sustainability of intensification underway in the African smallholder sector using a uniquely detailed panel survey that combines remote sensing data, soil analysis, yield cuts, GPS area measurements, and detailed field management surveys. Specifically, we quantify the on-farm yield response to nitrogen (N) fertilizer in relationship to 16 soil and field management regimes, adding to the scant literature that combines precise and objective measures of inputs, outputs, and ecological conditions on fields managed by farmers. Furthermore, we examine drivers of soil health using a measure of labile carbon that, unlike total carbon, can be responsive to farm management over the observable time period. Results are based on a representative sampling of Malawi's diverse agroecosystems through a multi-year study for over 1000 fields. We find surprisingly low yield response to N applications, highlighting that fertilizer access alone is not sufficient for sustainable intensification. We find complimentary "good agronomy", including effective weed management, crop rotations, and organic fertilizer applications are positive influences on maize yield response to inorganic fertilizers. Encouragingly, results show management practices such as incorporating diverse crop residues and manure for a few years can raise labile carbon levels, improving the soil base on which factors jointly determine yields. These findings underscore the importance of education, livestock and crop diversification, and farmer utilization of good agronomy to improve fertilizer use efficiency as a means to promote sustainable agricultural productivity.